Consumer brandswitching behavior: evidence from Malaysian smartphone users / Quah Li Ling, Santhi Govindan and Ravindran Radhakrishnan - Li Ling, Quah; Govindan, Santhi; Radhakrishnan, Ravindran (2018)
The flagship smartphone war switches battle grounds lead top brands vendor's market share in Malaysia has declined. Furthermore, researchers found that Malaysians change their mobile phones more frequently than other technology devices. Therefore, there will be chances for smartphone users to switch brand when they are considering to replace their phone. As such, understanding the dynamics behind brand switching has become a growing concern for smartphone marketeers. The aim of this study is to examine the factors affecting brand switching among smartphone users. This study has viewed various factors that might affect consumer brandswitching towards smartphone namely price, brand image, product features and sales promotion. A total number of 150 respondents were sampled using quota sampling technique. The research instrument utilized in this study was questionnaire and distributed at the malls in Penang. The results obtained were analyzed using frequency analysis, reliability analysis and multiple linear regressions. The finding of this study was that brand image and product features had significant relationship with brand switching. It is found that product features had strongest relationship with consumer brandswitching behaviour in purchasing smartphones. However, price and sales promotion was found to have no significant relationship with brand switching. Therefore, this study would benefit marketeers to understand which factors are influencing the consumer brandswitching behavior and which of the factors carry the most impactful relationship, and thus help them to develop a strategy in order to be successful in retaining their customers.